2005
DOI: 10.1111/j.1469-0691.2005.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of broth enrichment and real-time PCR to exclude the presence of methicillin-resistant Staphylococcus aureus in clinical samples: a sensitive screening approach

Abstract: A rapid and sensitive method for excluding the presence of methicillin-resistant Staphylococcus aureus (MRSA) in clinical samples was developed and evaluated. The method utilised an MRSA-selective enrichment broth for 16 h, followed by PCR quantification of the nuc gene. Samples below a quantitative PCR threshold were reported as MRSA-negative. Broths from PCR-positive samples were subcultured for MRSA isolation. Clinical samples (n = 334) in a constructed high prevalence population were analysed in parallel w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
0
28
1
Order By: Relevance
“…Since optimal screening for MRSA colonization is not limited to the testing of nasal swab specimens, alternative approaches that allow pooling of multiple specimens and testing of the pooled specimens in a single PCR are desirable. Use of a broth-PCR method for detection of MRSA has been described previously and has been implemented for routine screening for MRSA colonization (24). By this approach, a quantitative real-time PCR assay for detection of nuc is required to differentiate the growth of MRSA from that of MSSA from clinical specimens pooled in a selective broth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since optimal screening for MRSA colonization is not limited to the testing of nasal swab specimens, alternative approaches that allow pooling of multiple specimens and testing of the pooled specimens in a single PCR are desirable. Use of a broth-PCR method for detection of MRSA has been described previously and has been implemented for routine screening for MRSA colonization (24). By this approach, a quantitative real-time PCR assay for detection of nuc is required to differentiate the growth of MRSA from that of MSSA from clinical specimens pooled in a selective broth.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of MRSA colonization within 24 h would facilitate identification of carriers and allow the early implementation of isolation precautions for colonized patients in hopes of preventing spread to other patients. Several nucleic acid amplification-based assays for detection of MRSA from clinical specimens or for culture confirmation have been described (6,9,10,12,24,25,31). The IDI-MRSA assay (GenOhm, San Diego, CA) is a multiplex qualitative real-time PCR assay for detection of MRSA from nasal swabs.…”
mentioning
confidence: 99%
“…aureus was detected by a SybrGREEN ® real-time PCR assay targeting the nuc gene (Nilsson et al, 2005) in a LightCycler instrument (Roche Diagnostics, Bromma, Sweden).…”
Section: Detection Of S Aureus and Mrsa Using Real-time Pcrmentioning
confidence: 99%
“…The pellet was resuspended in LB medium, supplemented with 3 μg ml −1 cefoxitin and 8 μg ml −1 aztreonam, and incubated at 35 °C for 24 h. After cultivation on MRSA selective medium (Oxoid, Cambridge, UK & BioRad, Hercules, CA, USA), colonies suspected to be MRSA were subcultivated on S. aureus chromogenic medium (BD), Mannitol Salt Agar medium (76 mg ml −1 Mannitol Salt Agar, Mast Group Ltd., Bootle, UK), and MRSA selective medium (Oxoid), and tested for DNase activity (39 mg ml −1 DNase agar, Oxoid). Resistance test for cefoxitin by disc diffusion (Oxoid) on ISO-sensitest medium (31.4 mg ml −1 ISO-sensitest agar, Oxoid), as well as molecular identification by mec/nuc PCR (Nilsson et al, 2005), was undertaken on colonies identified as S. aureus, and potentially MRSA. Clonal relationships were disclosed through spa typing (Harmsen et al, 2003).…”
Section: Isolation and Characterisation Of Mrsa Strains From Wastewatermentioning
confidence: 99%
“…Screening for possible colonization of patients (n ϭ 24), staff (n ϭ 50), and family members of colonized staff (n ϭ 6) was performed. Swab (Copan, Brescia, Italy) samples (n ϭ 229) from throat, anterior nares, and groin were cultured in broth, and the presence of MRSA was verified in 37 broth samples from 12 individuals, by detection of nuc and mecA according to the method of Nilsson et al (9). One MRSA isolate from each individual was spa typed as described previously (3,4).…”
mentioning
confidence: 99%